Groundwater chemical and microbiological composition in Aptian-Cenomanian deposits (Kaimisovsky oil-gas bearing province); IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Nalivayko N. G. Nina Grigorievna; Dutova E. M. Ekaterina Matveevna; Spiridonov T. S. Timofey Sergeevich; Pokrovsky D. S.; Pokrovsky V. D. Vitaly Dmitrievich (Hydrogeochemistry and Hydrogeoecology, 2016)
Title screen